Professionalism or academicism in legal training - Vergara Lacalle, Óscar (Revista de derecho aragonés, 2022)
The Bologna Process has sought to bring about a shift in higher education along different lines. One of them is to empower the student as the agent of the learning process, under the classical idea that education is not a vase to be filled, but a flame to be lighted. In this way, the educational focus is directed towards the acquisition of competences by students rather than towards the mere gathering of inert knowledge. This paper addresses the problem of understanding these competences in an overly professionalising sense, as current institutional trends seem to require, under the intuition that the University misses something important when it leaves aside its essentially academic vocation and allows itself to be moulded by the changing and rushing demands of the markets.